Post-influenza bacterial infection: mechanisms of pathogenesis and advances in therapeutic strategies - Lei, Biao; Wang, Shun; Yu, Linzhong; Ma, Qinhai (Frontiers in Microbiology, 2025)
Patients coinfected with influenza virus (IFV) and bacteria face significantly elevated risks of critical illness and mortality. This vulnerability stems primarily from IFV-induced immunosuppression and disruption of respiratory barrier integrity. Specifically, prior IFV infection compromises the airway epithelium and impairs immune cell function, creating a permissive environment for secondary bacterial infections that drive severe disease progression. Within the lung, resident immune cells are crucial for pathogen surveillance, antibacterial defense, and homeostasis maintenance. However, recruited neutrophils and macrophages paradoxically become key drivers of detrimental immunopathology during coinfection. The literatures involved in influenza bacterial infection, influenza bacterial superinfection, post-influenza bacterial infection and secondary bacterial infection, were included. In this review, we summarize the literatures about epidemiology, treatment options and two pivotal mechanisms: The primary mechanisms of IFV-mediated susceptibility to bacterial infection, focusing on epithelial barrier damage and immune cell dysfunction; the central roles of specific immune cells (notably neutrophils and macrophages) and their effector pathways in fueling hyperinflammatory responses that cause severe immunopathology. A comprehensive understanding of the interactions between the pathogens and the host will assist in the development of therapeutic modalities for the prevention and treatment of post-influenza bacterial infection.